(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
The Ustyurt Plateau is considered a region rich in historical and cultural monuments. One of the greatest monuments of the plateau is the ancient settlement of Dauletkerey (Korgansha). Built in the Middle Ages on a caravan route, this settlement served to establish trade between nomadic tribes and sedentary peoples. According to local residents, the construction of this fortress is associated with the name of Alexander Bekovich-Cherkassky, who went to Khiva in 1717. However, both Russian expeditions and the results of subsequent archaeological research confirm that this monument was built during the heyday of the Khorezm state. Analyzing the data of Russian expeditions that crossed the Ustyurt plateau before the 20th century, the author finds out that there was a third caravan route.